Education.com
Try
Brainzy
Try
Plus
Tink7
Tink7 asks:
Q:

solve 4x - (6x-5) +3 = 1

In Topics: School and Academics
> 60 days ago

|

Answers (1)

pigtoria
pigtoria writes:
Hi Tink7,

4x - (6x-5) +3 = 1

To solve the above equation, the first thing you do is remove the equation out of the parenthesis:

4x – 6x + 5 + 3 = 1

Then add the like terms together: (in other words, add the numbers with variables and numbers without the variables separately)

(4x – 6x) + (5+3) = 1

-2x + 8 = 1

Isolate the term with the variable by bringing the number to the other side of the equation

-2x = 1 – 8
-2x = -7

Solve for X by bringing the number 2 to the other side

x = 7/2

Plugging 7/2 into the original equation and check your answer:

4 (7/2) – 6 (7/2) + 5 + 3 = 1

28/2 – 42/2 + 5 + 3 = 1

14 – 21 + 5 + 3 = 1

-7 + 8 = 1

  1 = 1

Answer: X = 7/2
> 60 days ago

Did you find this answer useful?
1
yes
0
no
Answer this question